EFFECT OF STREBLUS ASPER LEAVES ON LOCOMOTION, ANXIETY AND COGNITION IN RATS - NEEKHRA, SACHIN; AWASTHI, HIMANI; SINGH, DCP (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The current study deals with the evaluation of neuropharmacological activities of hydroalcoholic extract of the plant Streblus asper. Methods: Hydroalcoholic extract of S. asper leaves was administered to animals at the dose of 200 and 400 mg/kg p.o., respectively. The neuropharmacological activities, namely, anxiolytic, muscle-relaxant, nootropic, and locomotor activities of hydroalcoholic extract of S. asper leaves were evaluated. The antioxidant activity of the hydroalcoholic extract of S. asper leaves was also investigated. Results: The dose 400 mg/kg p.o. of hydroalcoholic extract indicated significant variation with control group on neuropharmacological activity, especially nootropic and locomotion, whereas the mentioned dose did not show a significant effect on anxiolytic and muscle-relaxant activities. Percentage scavenging activities and inhibition concentration (IC50) were reported as 63.132 at 100 μg/ml and 35.33, respectively. Conclusion: It was found that hydroalcoholic extract of S. asper leaves can treat central nervous system disorders caused by oxidative stress.